Durability of clinical benefit with Stanford Neuromodulation Therapy (SNT) in treatment-resistant depression - Andrew D. Geoly; Katy H. Stimpson; Flint M. Espil; Brandon S. Bentzley; Nolan R. Williams (Brain Stimulation)
Background: Depression, the leading cause of disability worldwide, is a chronic disease characterized by a relapsing-remitting course. Acute treatments such as electroconvulsive therapy, ketamine, and repetitive transcranial magnetic stimulation are often effective at initiating remission, but relapse to a major depressive episode is common without ongoing interventions. Stanford Neuromodulation Therapy (SNT) produces high rates of remission after five days of acute treatment; however, the duration of this remission following a single course of SNT in people suffering from treatment-resistant depression is unknown, which poses a significant limit on clinical decision-making. Methods: Forty-six participants with treatment-resistant depression (TRD), received five days of SNT. Functional connectivity derived from resting-state functional MRI (fMRI) was used to individually target the region of the left dorsolateral prefrontal cortex most functionally anticorrelated with the subgenual anterior cingulate cortex. The 6-item Hamilton Depression Rating Scale (HDRS-6) was collected fortnightly for up to 24 weeks. Relapse was defined as two consecutive HDRS-6 scores of 5 or above. Results: Seventy percent (32 of 46) of participants entered remission the week following treatment. After 12 weeks of treatment, 15 of 46 (33 %) participants remained in remission. Of the participants who entered remission, 15 of 32 (47 %) remained in remission. Conclusions: At 12 weeks, a subset of participants remained in remission, suggesting that the durability of SNT warrants further study. Comparisons with conventional rTMS should be interpreted cautiously given differences in study design, populations, and outcome measures.